(untitled) (Società e diritti, 2019)
The Author examine Schauer’s last book "the Force of Law" and explain that the American philosopher is certainly not a fully-fledged normativist but he thinks that coercion is an element of the legal order and of law. The Author, however, suggest to leave aside the role of coercion in the law, and points out that Schauer’s book gives rise to various interesting reflections on law in general. In order to understand the need to use force within the law, it is useful to refer to Schauer’s analyses of the psychological attitudes of individuals and the extent to which these impinge upon their behavior with regard to the legal demands made by a society. In any case, the reasons of the Society must prevail over individual ones. Key words: the force of law, coercion, legal positivism